2020
DOI: 10.1021/acsomega.9b01665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HF on the Lithiation Behavior of the Silicon Anode in LiPF6 Organic Electrolyte Solution

Abstract: As one of the major impurities in the organic electrolyte, HF can react with the alkali components in the solid electrolyte interphase (SEI), such as lithium alkoxide and lithium carbonate, to form more LiF-rich SEI. Here, the effects of HF on the lithiation behavior of the single crystal Si(111) anode were studied using scanning electron microscopy, soft X-ray emission spectroscopy, and windowless energy-dispersive X-ray spectroscopy. When the Li−Si alloy is formed in 1.0 M LiPF 6 in the propylene carbonate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It is reported that LiF plays an important role in stabilizing the SEI and is beneficial to cycle stability . It is also generally known that LiF has negligible solubility in most electrolytes and could suppress electrolyte decomposition . Therefore, the introduction of the PO 3 group leads to an SEI film with a higher LiF content, which is closely related to its superior cycling stability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is reported that LiF plays an important role in stabilizing the SEI and is beneficial to cycle stability . It is also generally known that LiF has negligible solubility in most electrolytes and could suppress electrolyte decomposition . Therefore, the introduction of the PO 3 group leads to an SEI film with a higher LiF content, which is closely related to its superior cycling stability.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is widely believed that HF will attack the SEI on the anode surface and initiate further reaction between the active material and the electrolyte. 39,40 On the other hand, PF 5 and POF 3 will catalyze the ring-opening polymerization of EC or the decomposition of DEC, further generating more heat. 41 The addition of APTES reduces the effect of HF and POF 3 and their subsequent reactions.…”
Section: Characterizations For Enhanced Thermal Stability With the Ap...mentioning
confidence: 99%